ANALISIS KEBERHASILAN USAHA SIMPAN PINJAM BUMDES SUMBER REZEKI DESA RANTAU SAKTI - Lisa Ambarwati (Fakultas Ekonomi Universitas Pasir Pengaraian, 2023)
One of the Government's missions is to develop rural areas which can be achieved through community empowerment. The estuary of all village development is to provide opportunities for regional and rural capabilities and independence as the backbone of the regional and national economy. Economic progress at the provincial level can be achieved, if the districts and municipalities have good economic activities. BUMDES Sumber Rezeki was established on November 23 2011, based on Village Head Decree No. 09 of 2011 until now BUMDesa Sumber Rejeki has a main savings and loan business and plans to develop a business unit for bottled drinking water and LPG gas. The purpose of this research is to find out the success of the BUMDesa Sumber Rezeki Village Savings and Loansbusiness for the analysis of new business development that has been planned to be more effective. Methods of data analysis using multiple linear regression, while testing the hypothesis is done with the t-test using SPSS. This analysis is used to prove whether or not the performance variables of the Bumdes Sumber Rezeki Village Savings Loan business performance are significant. The results of the partial test research, namely the value of the t count> t table and the significant level is smaller than Alpha (0.05). So it can be concluded that Bumdes performance influences village economic development, in other words, the hypothesis is accepted. This is in accordance with the reality of observations in the field that although the efforts made by Bumdes in each village have not really been stretched, however, due to the contribution to Village Original Income it has been proven to have an effect on development in the village.